PENERAPAN PEACE EDUCATION DALAM KONTEKS NEGARA KONFLIK: SYSTEMATIC LITERATURE REVIEW - Labibatussolihah Labibatussolihah; Nour Muhammad Adriani (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
Historical trauma commonly occurs in countries that have experienced prolonged conflicto, such as civil war, genocide, and rule by authoritarian regimes. This trauma forms a collective memory of the wounds that occurred, resulting in prejudice, stereotypes, and intergroup tensions that lead citizens to an identity crisis. The process of healing these inherited psychological wounds requires efforts to reconstruct their social, political, and moral order. In this context, peace education is a primary approach to instilling the values ​​of tolerance, empathy, reconciliation, and social justice as the foundation for forming global citizenship oriented towards positive actions for the realization of a peaceful society. This study uses a Systematic Literature Review method on the Scopus database from 2020-2025, applying the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) using the keyword "peace education." A total of 2,787 articles were obtained, which were then reduced to a focus on conflict-affected countries including Rwanda, Sierra Leone, Cambodia, and South Africa. The resulting nine articles were selected for further in-depth analysis. The result finds that: 1) historical background influences the implementation of peace education in post-conflict countries; (2) peace education contributes to the development of conflict resolution capabilities; (3) a multi-perspective approach has positive and negative impacts; (4) peace education through affective recognition forms empathy and emotional bonds across generations; (5) there is a need for the involvement of various parties at the local, national and international levels in the implementation of peace education in post-conflict countries. ABSTRAK Trauma sejarah umumnya terjadi di negara-negara yang telah mengalami konflik berkepanjangan seperti perang saudara, genosida, dan dikuasi oleh rezim yang otoriter. Trauma ini membentuk memori kolektif akan luka yang terjadi sehingga muncul prasangka, stereotipe, dan ketegangan antar kelompok yang menjadikan warga negara krisis identitas. Proses penyembuhan akan luka psikis yang diwariskan ini memerlukan upaya rekonstruksi kembali tatanan sosial, politik, dan moral mereka. Dalam konteks tersebut, peace education menjadi pendekatan utama untuk menanamkan nilai toleransi, empati, rekonsiliasi, serta keadilan sosial sebagai dasar pembentukan global citizenship yang berorientasi pada tindakan positif demi terwujudnya masyarakat yang damai. Studi ini menggunakan metode Systematic Literature Review pada basis data scopus pada tahun 2020-2025 dengan menggunakan Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) melalui kata kunci “peace education”. Diperoleh 2787 artikel yang kemudian direduksi dengan fokus pada negara-negara konflik diantaranya Rwanda, Sierra Leone, Kamboja, dan Afrika Selatan yang hasilnya 9 artikel terpilih untuk dianalisis lebih mendalam. Hasil kajian mengungkapkan: 1) latar belakang historis mempengaruhi penerapan peace education dinegara pasca konflik; (2) peace education berkontribusi terhadap pembentukan kemampuan resolusi konflik; (3) pendekatan multiperspektif memberikan dampak positif dan negative; (4) peace education melalui affective recognition membentuk empati dan ikatan emosi lintas generasi; (5) perlu adanya keterlibatan berbagai pihak ditingkat local, nasional, dan internasional dalam penerapan peace education di negara pasca konflik.